Early Introduction and Cumulative Consumption of Sugar-sweetened Beverages during the Pre-school Period and Risk of Obesity at 8–14 years of Age - Cantoral, Alejandra (Pediatr Obes, 2015)
BACKGROUND: Consumption of sugar-sweetened beverages (SSB) has been associated with risk of obesity, but little evidence exists to evaluate if age of introduction and cumulative SSB consumption increases risk in children. OBJECTIVES: To estimate the relationship between age of introduction and cumulative SSB consumption with the risk of obesity in a cohort of 227 Mexican children. METHODS: SSB intake was measured every six months; age of introduction and cumulative consumption during the pre-school period were calculated. Height, weight, waist circumference, SSB intake and other relevant variables were measured at age 8–14 years and obesity defined using standard criteria. RESULTS: All participants were introduced to SSB before age 24 months and most (73%) before 12 months. Early SSB introduction (≤12 months) was not significantly associated with increased odds of obesity (OR=2.00, 95% CI: 0.87, 4.59). However, children in the highest tertile of cumulative SSB consumption, compared to the lowest, had almost three times the odds of general (OR=2.99, 95% CI: 1.27, 7.00) and abdominal (OR=2.70, 95% CI: 1.03, 7.03) obesity at age 8–14 years. CONCLUSIONS: High SSB consumption increased the likelihood of obesity in 8–14 year-old children. Our results suggest that SSB intake should be delayed and excessive SSB consumption in pre-school period should be avoided.